Comparative Analysis of Democratization and Civil-Military Relations in Turkey and South Korea till early 2000s - Giray Sadık (Gazi Akademik Bakış)
In the process of achieving political, economic and social development, the essence of establishing sound civilian rule remains as one of the key factors in consolidating democracy alongside with reinforcing socio-economic factors. This process becomes ever more challenging as the developing countries are in desperate need to attain political and economic modernization simultaneously. In order to address this heated debate on the civil-military relations in developing countries the article undertakes to present a comparative insight on the role of the civil-military relations in socio-political and economic development by tracing the emerging motivations and balances for military’s involvement in politics. Although having markedly divergent historical backgrounds, Turkey and South Korea constitute leading examples for developing countries in the different regions of the world. Alongside with broadly common – developing country – notion, the development of civil-military relations in both countries provides substantial ground for comparison of the role of military in the modernization and democratization processes of these countries till early 2000s. With the aim of tracking the reasons and repercussions of military’s increasingly milder influence over politics the article begins with the introduction of theoretical framework for comparative analysis, and then proceeds with the application of comparative framework followed by the brief historical overviews of civil-military relations of respective countries. In the analysis part, the impacts of endogenous and extraneous factors to civil-military relations are comparatively examined. In order to track the motives and restrains for varying forms of military influence in the political processes of these developing countries the study employs Sundhaussen’s “Endogenous and Extraneous Factors”. Finally, the conclusion summarizes comparative findings, while outlining the implications of emerging civil-military relations in the development and democratization processes of these countries.